PROMOTION OF TOURIST VISITS AT THE SILOKEK GEOPARK, SIJNJUNG DISTRICT, WEST SUMATRA PROVINCE - Fidya Fadillah; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Silokek Geopark is one of the geoparks located in the Sijunjung Regency, West Sumatra Province. The various tourism potentials owned by the Silokek Geopark tourist attraction are the initial capital for tourism development in the area. However, relying on natural and cultural potential alone is not enough to make tourists visit, therefore marketing activities are needed in the form of promotions. Promotion is one of the activities of introducing a tourist attraction so that it can be known by the wider community both domestically and internationally. This study aims to determine promotional efforts in increasing tourist visits at the Silokek Geopark tourist attraction and to find out the obstacles in increasing promotion at the Silokek Geopark. This study uses a qualitative method with a descriptive approach to describe the actual situation by collecting data from observation, documentation and interviews. The key informants in this study were the Silokek Geopark tourist attraction manager and the Sijunjung Regency Tourism Office. From this study it can be seen that the promotions carried out by Silokek Geopark are individual sales, advertising, sales promotion, direct marketing, and public relations. Keywords: Promotion, Tourism Object, Silokek Geopark